Quantitative Southern blot analysis in the dystrophin gene of Japanese patients with Duchenne or Becker muscular dystrophy: a high frequency of duplications. Issue 12 (December 1992) - Hiraishi, Y; Kato, S; Ishihara, T; Takano, T
Abstract : Eighty-four unrelated patients with Duchenne or Becker muscular dystrophy in Japan were studied by quantitative Southern blot analysis with dystrophin cDNA probes. We found partial deletions and duplications in 47 (56%) and 12 (14%) cases respectively by HindIII digestion. The duplications were confirmed by BglII digestion and densitometric scanning. The frequency of duplications in this study is significantly higher than those previously reported. This may be because of the small sample number, the racial difference, or our quantitative methods. Our results suggest that attempts to detect duplications are important for a precise diagnosis. Both deletions and duplications clustered at the two hot spots as reported previously. Six cases were exceptions to the 'reading frame hypothesis'. We detected three types of HindIII RFLP. Based on the results of one duplication case, we propose a revised sequential order of exons in the cDNA10 region of the dystrophin gene.